Tuberculous lymphadenitis of the head and neck in Canadian children: Experience from a low-burden region. (December 2016) - Xu, Jason J.; Peer, Shazia; Papsin, Blake C.; Kitai, Ian; Propst, Evan J.
Abstract: Background: Children are more likely than adults to develop extra-pulmonary tuberculosis (EPTB), which often presents as cervical lymphadenopathy. The role of surgery in management is uncertain. We reviewed all head and neck EPTB cases presenting to our tertiary care pediatric institution over a twelve-year period. Methods: All children 18 years of age and younger with EPTB involving the head and neck were included. We recorded clinical data and age at diagnosis, birth country, BCG vaccination status, as well as radiographic, surgical, histological, and microbiological results. Results: All 16 patients presented with cervical lymphadenopathy. Fourteen were born outside of Canada in TB endemic areas and all had foreign-born parents. Diagnosis was confirmed microbiologically from lymph node biopsies in 14 cases. Multi-drug resistant TB was identified in two cases: both had previous excisional node biopsies that had not been cultured. Two patients had culture negative suppuration despite adequate anti-tuberculous treatment that required surgery for cure. Conclusion: Ongoing suppuration despite appropriate drug therapy is seen in a minority of patients. We found that excisional lymph node biopsy of diseased cervical lymph nodes is diagnostic, and also therapeutic in some cases with ongoing suppuration despite appropriate drug therapy. Mycobacterial culture of lymph nodes is important for diagnosis and determination of drug resistance patterns.